RESULTS OF THE STUDY OF THE LIGHT FLY FAUNA (LEPIDOPTERA, PYRALOIDEA) OF THE "MYKHAYLIVSKA TSILINA" NATURE RESERVE IN 2022 - ГОВОРУН, Олександр (ВПЦ "Київський університет" - Publishing center "Kyiv University", 2025)
Background. Studies of the nocturnal Lepidoptera fauna of the Mykhailivska Tsilyna reserve were fragmentary until 2000. The species composition of most butterflies groups still remain unexplored on this territory. In addition to the butterflies of the bombycoid complex the fauna of only Pyralidae family has been studied in detail on the territory of the reserve. Studies of pyralids species composition on the Mykhailivska Tsilyna territory began in 2002 and continue to this day (Govorun, 2009-2021; Govorun, Parkhomenko, 2003; Nadvorny, 1993). The paper presents a general list of registered Pyralidae species and the results of its study in 2022. Methods. The moths were collected during three trips: July 13-15, July 29-31, August 27-28, 2022, in Velyki Luky village (in the area of ​​the reserve's field office, 50°44′44″N, 34°9′48″E), as well as in the steppe area (50°44'53.7"N, 34°10'55.7"E). With the onset of dusk, one or two 250 W mercury arc lamps were turned on, fixed at a height of 2-2.5 m from the soil surface against the background of white screens. The caught butterflies were immediately placed in mordants filled with ethyl acetate. At dawn, the lights were turned off. Insects were mounted on entomological needles or placed in mattresses for further identification. Results. A total of 367 fireflies were collected in the reserve during the year. In total, 55 Pyralidae species from 2 families and 8 subfamilies were discovered in 2022. Materials from previous years that were not included in previous publications were also processed. Сonclusions. The work planned in the territory organization project to reduce tree cover and remove forest belts will likely lead to a biodiversity decrease on this territory. At the same time, further overgrowth of the steppe will reduce the butterfly species number, the development of which is associated with steppe vegetation. In our opinion, it is necessary to stop and prevent further afforestation of the reserve territory. This can be done by applying one of the following methods: periodic mowing of steppe areas that are still preserved; moderate grazing of cattle; introduction into the territory and provision of living conditions for a wild population of large ungulates; periodic controlled burning of individual areas in the fall.

Вступ. Дослідження фауни нічних лускокрилих заповідника «Михайлівська цілина» до 2000 р. носили фрагментарний характер, при чому видовий склад більшості груп метеликів ще й досі залишається недослідженим. Крім метеликів бомбікоїдного комплексу, на території заповідника детально досліджено фауну лише представників родини Вогнівки. Дослідження видового складу вогнівок на території заповідника «Михайлівська цілина» розпочато у 2002 р. та продовжується дотепер (Говорун, 2009-2021; Говорун, Пархоменко, 2003; Надворный, 1993). В роботі представлено загальний список зареєстрованих видів та результати дослідження вогнівок у 2022 р. Метою роботи за програмою науково-дослідної лабораторії «Моніторингу популяцій тварин та рослин Сумської області» у 2022 р. було продовження дослідження фауни лускокрилих на території природного заповідника «Михайлівська цілина». Методи. Вогнівок було зібрано під час трьох виїздів: 13-15 липня, 29-31 липня, 27-28 серпня 2022 р. в с. Великі Луки на ділянці польового офісу заповідника (50°44′44″п.ш., 34°9′48″сх.д.), а також на ділянці степу (50°44'53.7" п.ш.,  34°10'55.7" сх.д.). Із настанням сутінок вмикали 1-2 дугово-ртутні лампи 250 W, зафіксовані на висоті 2-2,5 м від поверхні ґрунту на тлі білих екранів. Спійманих метеликів відразу поміщали в морилки, заправлені етилацетатом. На світанку світло вимикали. Комах монтували на ентомологічні голки або вкладали у матрацики для подальшого визначення. Результати. Всього під час досліджень у 2022 р. на території заповідника зібрано 367 вогнівок. Серед них виявлено 55 видів з 2 родин та 8 підродин. До того ж опрацьовано матеріали попередніх років, які не було включено в попередні публікації. Висновки.  В існуючому проекті організації території Природного заповідника «Михайлівська цілина» заплановано роботи по зменшенню порості дерев та видаленню лісосмуг, що вірогідно призведе до зменшення біорізноманіття на цій території. В той же час подальше заростання степу знизить чисельність та кількість видів метеликів, розвиток яких пов’язано зі степовою рослинністю. На нашу думку, зупинити існуюче та попередити подальше заліснення заповідної території можливо періодичним викошуванням степових ділянок, які ще збережено; помірним випасом великої рогатої худоби; запуском на територію (і забезпеченням умов для проживання) дикої популяції великих копитних; періодичним контрольованим випалюванням окремих ділянок восени.
РЕЗУЛЬТАТИ ДОСЛІДЖЕННЯ ФАУНИ ВОГНІВОК (LEPIDOPTERA, PYRALOIDEA) ПРИРОДНОГО ЗАПОВІДНИКА «МИХАЙЛІВСЬКА ЦІЛИНА» У 2022 РОЦІ
Keywords: заповідні території; фауна; багаторічні дослідження; Lepidoptera; заповідні території; фауна; багаторічні дослідження; Lepidoptera; protected areas; fauna; long-term research; Lepidoptera